THE INFLUENCE OF SALES GROWTH, LEVERAGE, COMPANY SIZE, AND PROFITABILITY ON TAX AVOIDANCE IN CONSUMER NON-CYCLICALS COMPANIES FROM 2021 TO 2023 - Dintia, Cecilia; Santioso, Linda (Graduate Program of Universitas Tarumanagara, 2025)
The purpose of this study is to gather empirical data regarding the effects of sales growth, leverage, company size, and profitability on tax avoidance. Focusing on consumer non-cyclicals companies that listed on the Indonesia Stock Exchange (IDX), the study used a purposive sampling method to select a data set of 124 samples from 52 companies covering the period 2021 to 2023. To analyze the data, SPSS version 25 was employed, and multiple linear regression analysis was applied to examine the relationships among these variables. The findings indicate that sales growth has a positive effect on tax avoidance. Conversely, profitability shows indicates a detrimental effect on tax avoidance. Meanwhile, leverage and company size were found to have no significant effect on tax avoidance within the sample. This study aims to contribute to the literature on tax avoidance by clarifying the role of specific financial factors in influencing tax strategies among consumer non-cyclicals companies in Indonesia. The expectation is to minimize tax avoidance actions that could result in significant losses to the state. The insights provided can serve as valuable references for managers and policymakers, helping them to understand the financial characteristics that drive tax avoidance behavior. Additionally, this research encourages further exploration into other factors that may influence tax avoidance, ultimately supporting a more comprehensive understanding of corporate tax practices.